Serine/threonine phosphatase 5 (PP5C/PPP5C) regulates the ISOC channel through a PP5C‐FKBP51 axis. (1st February 2018) - Hamilton, Caleb L.; Abney, Kevin A.; Vasauskas, Audrey A.; Alexeyev, Mikhail; Ni, Li; Honkanen, Richard E.; Scammell, Jonathan G.; Cioffi, Donna L.
Abstract : Pulmonary endothelial cells express a store‐operated calcium entry current ( I soc ), which contributes to inter‐endothelial cell gap formation. I soc is regulated by a heterocomplex of proteins that includes the immunophilin FKBP51. FKBP51 inhibits I soc by mechanisms that are not fully understood. In pulmonary artery endothelial cells (PAECs) we have shown that FKBP51 increases microtubule polymerization, an event that is critical for I soc inhibition by FKBP51. In neurons, FKBP51 promotes microtubule stability through facilitation of tau dephosphorylation. However, FKBP51 does not possess phosphatase activity. Protein phosphatase 5 (PP5C/PPP5C) can dephosphorylate tau, and similar to FKBP51, PP5C possesses tetratricopeptide repeats (TPR) that mediate interaction with heat shock protein‐90 (HSP90) chaperone/scaffolding complexes. We therefore tested whether PP5C contributes to FKBP51‐mediated inhibition of I soc . Both siRNA‐mediated suppression of PP5C expression in PAECs and genetic disruption of PP5C in HEK293 cells attenuate FKBP51‐mediated inhibition of I soc . Reintroduction of catalytically competent, but not catalytically inactive PP5C, restored FKBP51‐mediated inhibition of I soc . PAEC cell fractionation studies identified both PP5C and the ISOC heterocomplex in the same membrane fractions. Further, PP5C co‐precipitates with TRPC4, an essential subunit of ISOC channel. Finally, to determine if PP5C is required for FKBP51‐mediated inhibition of calcium entry‐induced inter‐endothelial cell gap formation, we measured gap area by wide‐field microscopy and performed biotin gap quantification assay and electric cell‐substrate impedance sensing (ECIS®). Collectively, the data presented indicate that suppression of PP5C expression negates the protective effect of FKBP51. These observations identify PP5C as a novel member of the ISOC heterocomplex that is required for FKBP51‐mediated inhibition of I soc .